Analyzing the effects of powder and post-processing on porosity and properties of electron beam melted Ti-6Al-4V. Issue 7 (3rd November 2017) - Cunningham, Ross; Nicolas, Andrea; Madsen, John; Fodran, Eric; Anagnostou, Elias; Sangid, Michael D.; Rollett, Anthony D.
ABSTRACT: Metal additive manufacturing techniques such as the powder-bed systems are developing as a novel method for producing complex components. This study uses synchrotron-based X-ray microtomography to investigate porosity in electron beam melted Ti-6Al-4V in the as-built and post-processed state for two different powders. The presence of gas porosity in the starting powder was shown to correlate to porosity in the as-built components. This porosity was observed to shrink after a hot isostatic press treatment, but grow following a subsequent heat treatment. Crystal plasticity simulations were used to observe the effects of various observed pore sizes on mechanical behavior under loading. GRAPHICAL ABSTRACT: IMPACT STATEMENT This work combined µSXCT and crystal plasticity simulations to characterize porosity through each processing stage of EBM Ti-6Al-4V. Gas porosity was detected in the as-HIPed state, and growth was observed after subsequent heat treatment.